Protein-A and peanut agglutinin binding lymphocytes in the peripheral blood and lymphoid tissues of goats - SARMAH, A K; BANSAL, M P (The Indian Journal of Animal Sciences, 2013)
Lymphocyte subpopulations of peripheral blood, and various lymphoid tissues of adult, kid and foetal goats were characterized on the basis of their binding on protein-A and peanut agglutinin. In adult goats and kids, protein-A binding cells were numerous in spleen than in the peripheral blood and other lymphoid tissue. In foetal goats, the highest percentage of protein-A binding cells were found in the Iymphnodes. PNA binding cells were found in highest number in the peripheral blood than in the spleen and Iymphnodes of adult goats. In kids and foetal goats, the lymphoid tissues other than the thymus had conspi~uously less number of PNA binding cells than the adult counterparts.